Modelling and control in biomedical systems 2006 (including biological systems) : a proceedings volume from the 6th IFAC symposium, Reims, France 20-22 September 2006 /: a proceedings volume from the 6th IFAC symposium, Reims, France 20-22 September 2006. (2006) - Unknown
No abstract available